International Labour Migration: Economic Aspects - Marinov, Velko (Research Papers, 2007)
The paper researches one of the forms of contemporary international economic relations. It presents a short review of the key concepts of the international labour migration and outlines the economic factors of its development, the stages of this process, the typical features of the most recent labour migration, its quantitative and territorial parameters.The paper gives a detailed account of the economic effects of the international labour migration nationally and worldwide (in terms of global economy). The effects of the global labour migration on national economies are interpreted in the context of the immigration countries and the emigration countries of origin.The author analyses the Republic of Bulgaria’s participation in the international labour migration. An attempt has been made to establish the factors contributing to a sizable emigration of the workforce from the country after 1990, with an outline of the economic specifics of the labour emigration from Bulgaria. Based on relatively limited information, the paper features the basic demographic and economic effects of the emigration of human resources from Bulgaria. The paper argues the necessity of developing of a viable migration policy of Bulgaria and formulates some fundamental requirements which the migration policy of the country should meet.